Enhancing Employee Performance Through Work Discipline and Motivation at UPTD Puskesmas Klari, Karawang - Fauziah, Ershi Hidayanti; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
The purpose of this research is to identify and analyze how Work Discipline and Work Motivation Influence Employee Performance at the UPTD Community Health Center in Klari District, Karawang Regency. This research is quantitative in nature and employs a causal method by conducting a survey among employees of the UPTD Community Health Center in Klari District, Karawang Regency. The research involves 61 employees of the UPTD Community Health Center in Klari District, Karawang Regency, selected through non-probability sampling techniques. Initial data obtained through questionnaires are utilized. The analysis employs multiple regression, coefficient of determination, hypothesis testing, and correlation. The research findings indicate that Work Discipline and Work Motivation have a significant influence on employee performance collectively; individually, Work Discipline and Work Motivation have a significant influence on employee performance. Additionally, it is proven that Work Discipline and Work Motivation significantly enhance employee performance. This research only addresses two influencing variables, thus additional research on variables and research methods will be conducted. The findings of this research can be utilized by institutions to consider factors that can improve employee performance. Future Research: Considering the unique features of the company under study, further research is expected to encompass more investigated variables. This research involves employees of the UPTD Community Health Center in Klari District, Karawang Regency, regarding performance, work motivation, and work discipline.